Enhancing electrode properties for high-performance fabric supercapacitors using rice straw-derived biochar - Alzate, David Joseph G.; Peñafiel, Felicidad Christina R.; Binag, Christina A. (2025)
Supercapacitors have high power and long cycle lives and can use renewable materials like biochar. This study explores the use of biochar derived from rice straw, an abundant agricultural waste, to enhance fabric-based supercapacitors. Rice straw was processed into biochar via nitric acid treatment (RSB), followed by pyrolysis under N2atmosphere, and then wet milled with 10% carbon black using a planetary ball mill (MRSB). The carbon material
was coated onto pineapple-cotton woven fabrics (PACF) via the dip-and-dry method, followed by in situ polymerization of pyrrole monomer to coat with polypyrrole (PPy). These electrodes were characterized and then assembled into symmetrical coin cell devices for electrochemical testing. Globular PPy was seen in the micrographs of the composites, preferring to form on and around RSB and MRSB. Gas adsorption data analysis shows a large surface area and pore volume increase after milling the biochar. The PPy/RSB/PACF and PPy/MRSB/PACF show higher conductivity values (1.22 x 10–2 S cm–1 and 17.85 x 10–2 S cm–1, respectively) and areal capacitance values (309.77 mF cm–2 and 266.12 mF cm–2, respectively, at 5 mV s–1) compared to the PPy/PACF composites’ values (0.107 x 10–2 S cm–1 and 87.02 mF cm–2 at 5 mV s–1), indicating the positive interaction between PPy, RSB, and MRSB. A symmetrical coin cell supercapacitor was assembled using the fabric composites as electrodes. The PPy/MRSB/PACF devices demonstrated higher areal capacitance values (741.85 mF cm–2 at 1 mA cm–2), columbic efficiency (92.84%), specific energy (15.45 Wh kg–1), and specific power (199.69 W kg–1) over the other devices. These results show the positive and extensive effect of MRSB on the electrochemical performance of the composite electrodes, showing its great potential as active materials for energy storage applications, and adding value to waste rice straw.
Keywords: Pineapples; Pineapple; Pineapple leaf fiber; Biochar